2007
DOI: 10.5507/bp.2007.003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of esophageal cancer - an overview article

Abstract: Background: Esophageal cancer is one of the most serious tumor diseases worldwide, owing to its rapid development and fatal prognosis in most cases. To compare epidemiologic characteristics, data published by the International Agency for Research on Cancer, Lyon, France and data from Masaryk Memorial Cancer Institute, Brno, Czech Republic were used.Methods: We conducted a search of selected Czech and foreign literature focused on the epidemiology of esophageal cancer and its main risk factors.Results and Concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
2
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 13 publications
6
69
2
6
Order By: Relevance
“…Esophageal cancer remains one of the most fatal types of cancer worldwide, with an incidence on the rise (9). Despite clinical advances, esophageal cancer remains one of the leading causes of cancer-associated mortality (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esophageal cancer remains one of the most fatal types of cancer worldwide, with an incidence on the rise (9). Despite clinical advances, esophageal cancer remains one of the leading causes of cancer-associated mortality (31).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that dietary behavior is also associated with esophageal cancer (8). Despite recent advances in surgical techniques and treatment strategies for esophageal cancer, the five-year survival rate post-surgery is only 20-30% (9). Furthermore, conventional chemotherapeutic drugs used in esophageal cancer treatment, including cisplatin, often have severe side effects that limit their efficacy (10).…”
Section: Introductionmentioning
confidence: 99%
“…Seventy-five percent of patients die within one year after diagnosis (Hiyama et al, 2007), while five-year survival is less than 5%. The risk of developing esophageal cancer increases with age, and the highest incidence has been reported to be at the age of 50 to 70 years (Kollarova et al, 2007). Most patients diagnosed with esophageal cancer live in the so-called Asian esophageal cancer belt, including parts of northern Iran (Lam et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…1 Five-year survival is less than 5%. 2 Squamous Cell Carcinoma: The gross appearance varies according to whether it is detected in an early or an advanced stage of the disease. Among early SCC, polypoid, plaque-like, depressed and occult lesions have been described.…”
mentioning
confidence: 99%